Generation of clinical‐grade functional cardiomyocytes from human embryonic stem cells in chemically defined conditions. (9th June 2017) - Tan, Yuanqing; Han, Pengcheng; Gu, Qi; Chen, Gang; Wang, Lei; Ma, Ruoyu; Wu, Jun; Feng, Chunjing; Zhang, Ying; Wang, Liu; Hu, Baoyang; Li, Wei; et al.
Abstract: A highly efficient cardiac differentiation from human pluripotent stem cells (hPSCs) is achievable using existing methods, especially with the standard B27 induction system. However, bovine serum albumin (BSA), one of the essential ingredients in B27, may pose significant complications for clinical studies owing to its animal origin and potential risks of virus contamination. Furthermore, the high cost of the B27 induction system also limits the applications of hPSCs‐derived cardiomyocytes. Here, a BSA‐free and chemically defined medium has been developed for differentiating hPSCs to clinical‐grade cardiomyocytes, which generated over 80% cardiac troponin T (cTNT)‐positive cardiomyocytes with high yield. When engrafting the cardiomyocytes into the hearts of myocardial infarction model rats, the rats survived with significantly improved heart functions in Δ ejection fraction and Δ fractional shortening. Importantly, the human embryonic stem cell (hESC) line (Q‐CTS‐hESC‐2) chosen for differentiation was of a clinical‐grade maintained in defined xeno‐free conditions. Compliant with the biological safety requirements, the Q‐CTS‐hESC‐2‐derived cardiomyocytes have passed the sterility and pathogen criteria tests for clinical applications. This study reports, for the first time, the generation of clinical‐grade and functional cardiomyocytes from hPSCs where BSA‐free and chemically defined conditions were maintained throughout the whole process. This provides the possibility of future therapeutic use of clinical‐grade hPSCs‐derived cardiomyocytes in treating heart diseases. Copyright © 2016 John Wiley & Sons, Ltd.